Effect of Different Culture Conditions on Nutritional Value of Moina macrocopa as a Live Feed for Fish Fry Production - Neri, Therese Ariane; Rohmah, Zuliyati; Ticar, Bernadeth F.; Choi, Byeong-Dae (Journal of Agriculture & Life Science, 2020)
The effects of supplementing ESP-FM (Erythrobactor sp.), freshwater Chlorella (Chlorella sp.), and baker’s yeast (Saccharomyces cerevisiae) on the nutritional value and mass production of Moina macrocopa, which is used as a live feed for fish fry production, was investigated. Consequently, the effects of feeding the enriched M. macrocopa to the nutritional composition of larval rockfish (Sebastes schlegel) and carp (Cyprinus carpio) was also investigated. Maximum density of M. macrocopa was reached within 15-21 days after inoculation (0.5 to 22 individual/mL), at various temperatures, and either decreased or remained almost constantly thereafter. Protein content and amino acids composition of M. macrocopa were found to be influenced by their respective diets while lipid and ash contents did not considerably change. M. macrocopa fed with baker’s yeast were low in n-3 HUFA content, and those fed on the freshwater chlorella were high in the 18:2n-6 and 18:3n-3 HUFA content, and in cultures treated with ESP-FM were high content in n-3 HUFA. The utilization of M. macrocopa as a substitute fish feed for carp and rockfish showed the enrichment nutritional content.